Impact of Surgical Smoke on the Surgical Team and Operating Room Nurses and its Reduction Strategies: A Systematic Review - Amirmohammad Merajikhah; Behzad Imani; Salman Khazaei; Hamid Bouraghi (Tehran University of Medical Sciences, 2022)
Background: Surgical smoke is an integral part of surgical operations that the surgical team has been exposed to for so long. This study aimed to investigate the effects of smoke, on members of the surgical team. Methods: A systematic review was conducted focusing on the complexity of surgical smoke. PubMed, Scopus and web of science databases were searched until May 2020 without any time or language limitation. All documents were reviewed by title or abstract according to the search strategy. The screening process of articles was performed by two independent authors. The articles were selected according to the inclusion and exclusion criteria. Results: Overall, 37 studies in this systematic study were investigated. The effects of many surgical smokes were found in a nutshell including complications such as carcinogenic, toxicity, mutation, irritant, transmission of tumor cells, virus transmission, headaches, dizziness, sleepiness, headache, the bad odor in head hair, the tearing of the eye on the surgical team and staff. Conclusion: Surgical smoke, produced during surgical operations, is one of the risks and threats to which the surgical team and operating room staff are at risk then can affect the organs of different bodies from the body of all operating room staff and surgical team.